Modulating food craving-related neural oscillations using tACS: study protocol for a randomized sham-controlled trial - Ljubisavljevic, Milos; King, Fransina C.; Ismail, Fatima Yousif; Statsenko, Yauhen; Bashir, Shahid; Abdullah, Osama; Rokers, Bas (Frontiers in Human Neuroscience, 2025)
IntroductionFood addiction is characterized by heightened craving and impaired inhibitory control, contributing to compulsive eating and obesity. Existing behavioral and pharmacological interventions often fail to achieve lasting effects. Transcranial alternating current stimulation (tACS), by modulating neural oscillations and connectivity, offers a novel, non-invasive approach for regulating craving-related neural circuits.ObjectivesThis study aims to evaluate the effects of fixed-frequency tACS targeting the dorsal lateral prefrontal cortex (DLPFC), anterior cingulate cortex (ACC), and insula on food cravings, inhibitory control, and related neural oscillations. The trial will assess whether tACS can reduce craving intensity and enhance inhibitory performance in individuals with varying degrees of food addiction severity.MethodsWe will conduct a randomized, double-blind, sham-controlled trial involving 175 participants aged 20–55 years, stratified by food addiction status (FA+ vs. FA-) using the Yale Food Addiction Scale (YFAS 2.0). Participants will receive tACS at alpha (10 Hz) or theta (6 Hz) frequency over the DLPFC, ACC, or insula for seven consecutive days. Electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) will be conducted pre- and post-intervention. Primary outcomes include changes in craving intensity and inhibitory control. Secondary outcomes include alterations in neural oscillations and functional connectivity.DiscussionWe hypothesize that theta-tACS over the ACC and insula will enhance inhibitory control and interoceptive awareness, while alpha-tACS over the DLPFC will improve top-down regulatory processes. This protocol aims to clarify the neural mechanisms underlying food cravings and evaluate tACS as a promising intervention for compulsive eating.